2023
DOI: 10.1136/bmjopen-2022-064872
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacological interventions for managing sickle cell disease in children and adolescents: protocol for a systematic review with network meta-analysis

Abstract: IntroductionSickle cell disease (SCD), an inherited haemoglobinopathy, has important impact on morbidity and mortality, especially in paediatrics. Previous systematic reviews are limited to adult patients or focused only on few therapies. We aim to synthesise the evidence on efficacy and safety of pharmacological interventions for managing SCD in children and adolescents.Methods and analysisThis systematic review protocol is available at Open Science Framework (doi:10.17605/OSF.IO/CWAE9). We will follow intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This study was performed and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, Network Meta-analysis extension guidelines and Cochrane Collaboration recommendations [30][31][32] (PROSPERO registration: CRD42022328471). The protocol has been published 33…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, Network Meta-analysis extension guidelines and Cochrane Collaboration recommendations [30][31][32] (PROSPERO registration: CRD42022328471). The protocol has been published 33…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses, Network Meta‐analysis extension guidelines and Cochrane Collaboration recommendations 30–32 (PROSPERO registration: CRD42022328471). The protocol has been published 33 and is available online for consultation at Open Science Framework (DOI: 10.17605/OSF.IO/CWAE9). Two authors independently conducted all steps of the studies’ selection and data extraction.…”
Section: Methodsmentioning
confidence: 99%